Co-operation between companies and the advisory system in innovations – a comparative analysis of Northern Germany and Western Denmark - Andreas P. Cornett (European Regional Science Association (ERSA), 2004)
Innovations and the capacity to innovate are crucial factors in the development of a firm and its ability to adapt to changes in the external environment. Growing attention has been paid to the mechanisms facilitating innovation in firms, both in large, small and medium-sized enterprises. As a consequence, attention has been on the role of innovation policy in economic policy in general and regional development in particular. The aim of this paper is to analyze the linkages between the business advisory system's efforts to promote innovation and the innovative activity within the firm with special attention to small and medium sized enterprises. The main aspects addressed deal with entities and relations of the innovative environment. The focal point is the interaction between the analyzed business entity and the external environment as a part of a broader network of innovative relations covering intra-firm as well as extra-firm relations and processes. The paper will highlight three aspects of the topic: - In the first part of the paper concepts and policies of innovation are discussed with regard to their ability to influence economic development. - The second section is dedicated to an introduction to the role of the advisory system in the creation of a regional innovative business environment, and will in particular focus on the comparative analysis of regional systems of innovation in an organizational and structural perspective. - The next section analyzes the regional system of innovation based on a survey of manufacturing firms and advisory organizations in Western Denmark and Northern Germany. The essential objective of this survey is to identify the potential of, and the crucial obstacles to a proactive regional innovation policy, since previous studies have shown that in particular small firms have difficulties in using the advisory system and the services offered. Based on this analysis, the study aims at contributing to the ongoing discussion of the role of public support schemes in innovation and technology in a regional and organizational perspective, based on the comparative analysis of regions in two countries. Key words: Regional system of innovation - Advisory system - Business incubators and science parks - R & D programs
Keywords: 330; Regional system of innovation; Advisory system; Business incubators and science parks; R & D programs